(untitled) (Journal of the College of Basic Education, 2023)
The United States of America resorted to investing the results that resulted from the aggression The Tripartite (1) over Egypt in 1956, represented in the state of anger and resentment that the countries Arabia, and the decline of British and French influence in the Arab region, to make new strides It hastened to exploit these conditions to achieve its strategic goals in imposing its hegemony over other countries. region, announcing it